Reliability and validity of the Chronojump open-source jump mat system - Basilio Pueo; Alfonso Penichet-Tomas; Jose Jimenez-Olmedo (Termedia Publishing House, 2020)
Vertical jump performance is a commonly used test to measure lower-limb muscle power that is carried out with several types of equipment. The aim of this study was to validate an open-source jump mat (Chronojump Boscosystems) against a proprietary jump mat (Globus Ergo Tester). Sixty-three active sportsmen (age 23.3 ± 2.4 years) completed 8 maximal-effort countermovement jumps (CMJ). The heights of the 504 CMJ were measured from the two jump mats simultaneously. Reliability was examined with intra-class correlation coefficients (ICC), paired samples t-tests, coefficient of variation (CV) and Cronbach's α. Bivariate Pearson's correlation coefficient (r) was used to examine validity. Effects were evaluated using non-clinical magnitudebased inference. There was almost perfect agreement between instruments (ICC = 0.999−1.000, most likely positive 100/0/0). Paired t-test showed a mean difference of 0.03 ± 0.21 cm (90% CI -0.04 − -0.01) between